Status of 174 Mhz RF system for BEP - Biryuchevsky, Yu.A.; Gorniker, E.I.; Kendjebulatov, E.K.; Krutikhin, S.A.; Kurkin, G.Ya.; Petrov, V.M.; Pilan, A.M. (Вопросы атомной науки и техники, 2012)
The new RF system for the BEP storage ring (which is an injector of VEPP-2000 accelerating complex) will increase the particles energy in the BEP from 0.9 to 1 GeV. RF system operates at a frequency of 174 MHz and consists of an accelerating cavity, RF power generator and control system. Новая ВЧ-система накопителя БЭП (являющегося инжектором комплекса ВЭПП-2000) позволит увеличить энергию частиц в БЭП от 0,9 до 1 ГэВ. ВЧ-система работает на частоте 174 МГц и состоит из ускоряющего резонатора, ВЧ-генератора мощности и системы управления. Нова ВЧ-система накопичувача БЕП (що є інжектором комплексу ВЕПП-2000) дозволить збільшити енергію частинок БЕП від 0,9 до 1 ГеВ. ВЧ-система працює на частоті 174 МГц і складається з прискорюючого резонатора, ВЧ-генератора потужності і системи управління.